A Study on a Novel of Bharati Mukherjee’s 'The Tiger’s Daughter': Exploring the immigrant experience and identity formation in Bharati Mukherjee's 'The Tiger's Daughter' (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mukherjee’s writing largely reflects her personal experience of such febrile subjectivity in crossing cultural boundaries. In novels such as Jasmine, The Tiger’s Daughter, Wife and The Desirable Daughters, as well as in her award winning short stories, Indian born Mukherjee adds to her character’s multicultural background a delicate undercurrent of translational upsurge which sometimes expresses itself through violence and existential disorderliness. Mukherjee’s women characters such as Tara Cartwright, Dimple, Jasmine or Tara Chatterjee, all quest for a location and show a subaltern dread and anxiety to be visible. They are not concentric to adopt racial stereotype at the cost of identity. They accept a mutative change through displacement and replacement of culture. Here is the study of Bharati Mukherjee’s novel ‘The Tiger’s Daughter’ as an immigrant’s psyche. There is a strange fusion of the American ness and Indian ness in the psyche of protagonist Tara and they are always at a note of confrontation with each other. Neither can she take refuge in her old Indian self nor in her newly discovered American self. The outcome of this situation is her split up psyche.